The effect of educational interventions based on Health Belief Model (HBM) on puberty health behaviors in Tehran’s female elementary students, 2019. - Zahra Kazemi (آموزش بهداشت و ارتقاء سلامت ایران, 2020)
Background and Objective: Several studies indicate low knowledge and poor performance of girls in puberty and menstruation. Puberty complications are easily preventable. Consequently, present study mainly aims to determine the effect of educational interventions based on Health Belief Model (HBM) on puberty health behaviors in Tehran’s female elementary students, 2019.